Hydrogeological studies of the Sepidan basin to supply required water from exploiting water wells of the Chadormalu mine utilizing reverse osmosis (RO) method - Pooria Kianoush; Mohammad Reza Mahvi; Nasser Keshavarz Faraj Khah; Ali Kadkhodaie; Behshad Jodeiri Shokri; Shahab Varkouhi (Results in Earth Sciences)
Due to the lack of rainfall potential in Central Iran, the water scarcity is still the main problem of production in the country. Accordingly, the use of unconventional waters will be inevitable. This study presents the amount of water required by the Chadormalu mine from the water wells of the Sepidan Plain, as well as the deficit or excess for exploiting the complex and the water treatment plant by reverse osmosis (RO) method. These studies were carried out to manage the groundwater resources of the Sepidan and Saghand basins and include the water level variations of piezometers, the water consumption of exploitive wells, aqueducts, and the Sepidan River every month. Furthermore, a sample of complete chemical analysis of the aqueducts' Saghand basin and the water entering the RO and leaving it for environmental evaluations have been carried out each season. The average discharges of water wells in the Sepidan Plain were 86.45 and 82.28 l/s in 2221 and 2023, respectively. Moreover, the amount of water exploitation has been lower than the renewable (dynamic) reserves, which in the heart of the water intake has a uniform increase in the monthly hydrograph's water level. At the same time, the reduction of total dissolved solids (TDS) entering from exploitation water intakes to the amount of 580 mg/l indicates the principled exploitation of dynamic reserves. The RO unit's output had no effect on the quality of the Saghand Playa's water but improved it qualitatively.